RECENT UPDATE ON LIPOSOME-BASED DRUG DELIVERY SYSTEM - CHARUMATHY, A.; UBAIDULLA, U.; SINHA, PRIYANKA; RATHNAM, GRACE (International Journal of Current Pharmaceutical Research, 2022)
In this review article, liposome a novel drug delivery has been discussed, which is one among the various drug delivery system used to target the drug to a particular tissue. As the structural similarity between lipid bilayer and cell membrane, the liposome can easily penetrate and produce an effective delivery of the drug to such that a free drug would not able to penetrate. Some other drug delivery systems include niosomes, microparticles, resealed erythrocytes, pharmacosomes, etc. The term liposome meaning lipid body. Liposomes can also be able to encapsulate in both hydrophilic and hydrophobic materials and are utilized as drug carriers in drug delivery. This technology is very useful for the treatment of certain diseases. In this review, the preparation, evaluation and the applications of the liposomal drug delivery system for targeting various diseases are elaborately presented.